When, If Ever, May States Deploy Military Force Without Prior Security Council Authorization? - Thomas M. Franck (Washington University Journal of Law & Policy, 2001)
Were the Charter a static instrument bound exclusively to the textually expressed intent of its drafters, the profound incapacitation of the Security Council and the absence of a stand-by police force might have put paid to the Charter’s collective security system. Instead, the system has adapted, specifically by uncoupling Article 43 from Article 42 and by broadening the authority of states to act in self-defense under Article 51. These adaptions, brought about precedent-by-precedent, are worth noting.
Keywords: International security; Aggression (International law); Human rights; Armed Forces; United Nations. Security Council; United Nations. Charter; Humanitarian aid; Military intervention